2014
DOI: 10.3390/w6020324
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Sea Level Rise on Salinity Intrusion and Transport Time Scales in a Tidal Estuary, Taiwan

Abstract: Global climate change has resulted in a gradual sea level rise. Sea level rise can cause saline water to migrate upstream in estuaries and rivers, thereby threatening freshwater habitat and drinking-water supplies. In the present study, a three-dimensional hydrodynamic model was established to simulate salinity distributions and transport time scales in the Wu River estuary of central Taiwan. The model was calibrated and verified using tidal amplitudes and phases, time-series water surface elevation and salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Similarly, other studies also revealed the inverse relationship between salinity intrusion length and freshwater discharge. For example, recent numerical studies of Liu and Liu (2014) in Wu River system in Taiwan showed that the salinity intrudes further during dry seasons. Similarly, Rice et al (2012) found that in Chesapeake Bay, the salt intrusion is enhanced in dry periods compared with that of typical periods.…”
Section: Effect Of Important Parametersmentioning
confidence: 99%
“…Similarly, other studies also revealed the inverse relationship between salinity intrusion length and freshwater discharge. For example, recent numerical studies of Liu and Liu (2014) in Wu River system in Taiwan showed that the salinity intrudes further during dry seasons. Similarly, Rice et al (2012) found that in Chesapeake Bay, the salt intrusion is enhanced in dry periods compared with that of typical periods.…”
Section: Effect Of Important Parametersmentioning
confidence: 99%
“…Brackish water is mostly found in estuarine areas where seawater mixes with freshwater [8]. Other than estuaries, the elevated groundwater salinity can be observed in the regions where groundwater is in contact with evaporates formations, or mixed with high mineralized and deeper aquifers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Other than estuaries, the elevated groundwater salinity can be observed in the regions where groundwater is in contact with evaporates formations, or mixed with high mineralized and deeper aquifers [8,9]. The discharges from industrial effluents containing dissolved salts, leachates of saline soils and the runoff of salt deposits such as halite or gypsum that is present in the sedimentary rocks also increase the amounts of total dissolved salts and thus lead to the formation of brackish water [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These stimulated a major debate on quantifying climate change impacts in coastal regions, and sea level rise has been identified as a primary impact [1]. Various sources have confirmed the historical trends of sea level variations and have projected as high as 2-m sea level rise by the end of this century [2][3][4].…”
Section: Introductionmentioning
confidence: 99%